Mass balance, metabolism, and pharmacokinetics of [14C]amdizalisib, a clinical-stage novel oral selective PI3Kδ inhibitor for the treatment of non-hodgkin’s lymphoma, in healthy Chinese volunteers - Zhao, Chun-Yang; Zhang, Li-Jun; Sun, Chan; Yu, Cheng-Yin; Wang, Jian; Sai, Yang; Su, Wei-Guo; Chen, Qian; Wang, Wei; Jia, Jing-Ying; Liu, Gang-Yi; Liu, Yan-Mei (Frontiers in Pharmacology, 2024)
Introduction Amdizalisib (HMPL-689) is an ATP-competitive PI3Kδ inhibitor currently under investigation for treating Hodgkin’s lymphoma. This study aimed to evaluate the metabolism, excretion, pharmacokinetics, and safety profile of amdizalisib in healthy human subjects to support its clinical application. Methods This Phase I clinical trial included six healthy Chinese male volunteers who received a single oral dose of 30 mg/100 µCi [14C]amdizalisib suspension. Blood, urine, and fecal samples were collected to analyze pharmacokinetics, metabolic pathways, and excretion patterns. Results Amdizalisib was rapidly absorbed, with a median Tmax of 2.5 h. The Cmax of 244 ± 48.9 ng/mL, and AUC0-t was 1870 ± 474 h ng/mL after a single oral dose. The blood-to-plasma total radioactivity ratio ranged from 0.561 to 0.645, indicating no significant affinity of [14C]amdizalisib and its metabolites to blood cells and the radioactive material is mainly distributed in plasma. Excretion was primarily via feces and urine, with 62.08% ± 3.00% and 37.15% ± 2.84% of the dose recovered, respectively, and over 94% of the drug excreted within 96 h. The parent drug was the main radioactive component in plasma (51.45% of total radioactivity). Additionally, 11 metabolites were identified, and the metabolic pathways include oxidation on the benzene or pyrimidine rings and conjugation with cysteine or glucuronic acid. The major metabolites in plasma were the di-oxidized and hydrogenated product (M424) and the mono-oxidized product (M406-2), accounting for 16.67% and 20.91%, respectively. Both of them are also the major radioactive components in urine and feces, among of which M424 accounted for 21.01% and 14.26%, M406-2 accounted for 8.08% and 11.30%, of the administered dose in urine and feces, respectively. In addition, the di-oxidized and methylated product (M436) was one of the major metabolites in feces accounting for 17.7% of the administered dose. Few of the parent drug was found in urine and feces, suggesting primary metabolized in the liver. No serious adverse events or drug-related deaths occured, with diarrhea as the most common adverse event. Discussion These findings demonstrate that amdizalisib is rapidly absorbed, extensively metabolized, and primarily excreted via feces and urine, supporting its continued development as a potential therapeutic for Hodgkin's lymphoma. Systematic Review Registration: https://www.chinadrugtrials.org.cn/, identifier CTR20212448.